Modeling Internal Logistics by Using Drones on the Stage of Assembly of Products - Cordova-Gonzalez, F; Derpich-Contreras, I; Olivares-Chiappa, V; Sepulveda-Salas, J (Elsevier B.V., 2015)
The subject addressed in this paper is the issue of using an UAV type Quadcopter in the internal logistics within a manufacturing plant, particularly at the stage of assembly and /or customization of products. The vertical takeoff and landing, as well as horizontal flight, both with the characteristic of low speed and high precision, are major requirements for this work. The quadrotor architecture has been chosen for analysis because of its low dimensions, good maneuverability, simple mechanics and available payload capacity. As a major drawback, the high energy consumption when operating is a constraint to be modeled and optimized. In the first step, an internal logistics modeling is performed in order to determine the location of depots, clusters and sub-clusters; workstations are defined and routes are generated using a genetic algorithm for each quadcopter of a particular fleet. In a second step, the weight to be transported by each quadcopter is determined, depending on the assigned route and workstations that should go through the sequence either to remove materials (picking) or to deliver materials (delivery). In a third step, it is determined the electric power amount to be drained off the battery of every quadcopter for a given route depending on the weight carried, distance covered, number of workstations visited and the quadcopter aerodynamic efficiency. ©2015 Published by Elsevier B.V.